Air microbial sampling in operating theatres by active and passive methods: equation correlation from the GISIO-ISChIA study results and comparison with the EU GGMP recommendation, towards the definition of threshold values : Air microbial sampling in operating theatres: comparison between active and passive methods - Pasquarella, Cesira Isabella Maria; Auxilia, Francesco; Barchitta, Martina; Cristina, Maria Luisa; D'Alessandro, Daniela; Mura, Ida; Nobile, Marta; Veronesi, Licia; Albertini, Roberto; Agodi, Antonella (Acta Biomedica Atenei Parmensis, 2023)
The aim of this study was to calculate the equation of correlation between the microbial air contamination values obtained by active sampling (colony-forming units per cubic metre, CFU/m3) and by passive sampling (Index of microbial air contamination, IMA), by using the data from the ISChIA study, and to compare the values obtained with the recommended limits defined by the EU Guidelines to Good Manufacturing Practice (EU GGMP), 2008, for clean areas used to manufacture sterile medicinal products.Air sampling was performed during 335 elective prosthesis procedures. Correlation between CFU/m3 and IMA values was evaluated using the Spearman test; p